2021
DOI: 10.1101/2021.12.09.471931
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A fungal plant pathogen overcomesmlo-mediated broad-spectrum disease resistance by rapid gene loss

Abstract: Hosts and pathogens typically engage in an evolutionary arms race. This also applies to phytopathogenic powdery mildew fungi, which can rapidly overcome plant resistance and perform host jumps. Using experimental evolution, we show that the powdery mildew pathogen Blumeria graminis f.sp. hordei is capable of breaking the agriculturally important broad-spectrum resistance conditioned by barley loss-of-function mlo mutants. Partial mlo virulence is associated with a distinctive pattern of adaptive mutations, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 92 publications
(164 reference statements)
0
4
0
Order By: Relevance
“…Indeed, several mutational events were detected in these isolates, suggesting modulation or loss-of-function of a transcriptional regulator, an E3-ligase-like protein, and a protein of unknown function to contribute to partial virulence on mlo genotypes (Kusch et al, 2021).…”
Section: Rapid Breakdown Of Mlo-mediated Resistancementioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, several mutational events were detected in these isolates, suggesting modulation or loss-of-function of a transcriptional regulator, an E3-ligase-like protein, and a protein of unknown function to contribute to partial virulence on mlo genotypes (Kusch et al, 2021).…”
Section: Rapid Breakdown Of Mlo-mediated Resistancementioning
confidence: 99%
“…Interestingly, experimental evolution trials demonstrated that B . hordei can rapidly adapt to overcome mlo ‐based resistance (Kusch et al, 2021; Schwarzbach, 1979). In these experiments, less than 15 asexual passages or generations of selection on barley mlo mutant plants were sufficient to obtain and stabilize partially mlo ‐virulent isolates of B . hordei .…”
Section: Drivers Of Rapid Evolutionary Adaptation In Powdery Mildew F...mentioning
confidence: 99%
See 2 more Smart Citations